1994
DOI: 10.1128/mcb.14.1.744
|View full text |Cite
|
Sign up to set email alerts
|

The effector domain of Rab6, plus a highly hydrophobic C terminus, is required for Golgi apparatus localization.

Abstract: C-terminal lipid modifications are essential for the interaction of Ras-related proteins with membranes. While all Ras proteins are farnesylated and some palmitoylated, the majority of other Ras-related proteins are geranylgeranylated. One such protein, Rab6, is associated with the Golgi apparatus and has a C-terminal CXC motif that is geranylgeranylated on both cysteines. We Ras-related proteins are 21-to 25-kDa proteins which bind guanine nucleotides and have GTPase activity. On the basis of their sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 53 publications
2
31
1
Order By: Relevance
“…3A and B confirmed that the three different rab6 proteins are expressed in the Sf9 cells in similar amounts and in an native form as demonstrated by the GTPbinding and GTPase assays• To analyze the modification of the different rab6 proteins we used Triton X-114 extraction. It has previously been described that isoprenylated ras-like proteins are separated into the detergent-containing phase after lipid modification [17]. The results of the separation experiments are shown in Fig• 4A.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…3A and B confirmed that the three different rab6 proteins are expressed in the Sf9 cells in similar amounts and in an native form as demonstrated by the GTPbinding and GTPase assays• To analyze the modification of the different rab6 proteins we used Triton X-114 extraction. It has previously been described that isoprenylated ras-like proteins are separated into the detergent-containing phase after lipid modification [17]. The results of the separation experiments are shown in Fig• 4A.…”
Section: Resultsmentioning
confidence: 80%
“…4A, lanes 1-4. The Triton X-114 extraction demonstrates that most of the rab6 wt and rab6 T27N molecules are isoprenylated in infected insect cells [17]. The extent of modification depends on the period between infection and cell harvest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations